Association between knowledge, attitude, and intention to report child abuse among early childcare providers in Kelantan and cross-cultural adaptation of its instrument. - Ja’afar, Siti Mariam (2021)
Background: Younger children are often the victim of child abuse. However, most of the cases were not reported. According to the statistics from the Royal Malaysia Police Department, less than 1% of child abuse cases were reported by early childcare providers (ECPs) working in preschools under the Community Development Department (CDD) despite the increasing trend of child abuse every year. However, studies looking into this matter were limited. For this study, a cross-cultural adaptation of the Early Childhood Educators Child Abuse Questionnaire (ECECAQ) was done in the first phase while the Malay-validated ECECAQ was used in the second phase of the study. Objectives: This study aims to adapt, translate and validate the ECECAQ; to determine the level of knowledge and attitude of child abuse among ECPs in Kelantan; to determine the proportion of intention to report child abuse among ECPs in Kelantan; and to determine the association between demographic factors, knowledge, and attitude of child abuse with the intention to report among ECPs in Kelantan. Methods: This study was conducted in two phases. It involved ECPs working in preschools registered with the CDD in Kelantan from November 2018 till December 2020. The first phase was a cross-cultural adaptation of the ECECAQ to fulfill the first objective. The ECECAQ underwent a translation and validation processes following an established guideline. 218 respondents working in preschools in Kota Bharu and Tumpat districts participated in this phase of the study. The ECECAQ contains six sections namely (1) demographic profile; (2) reporting experience; (3) education and training experience; (4); attitude; (5) knowledge; and (6) vignettes. The attitude sections were scaled using a 5-point Likert scale ranges from 5 (strongly agree) to 1 (strongly disagree). Negatively phrases items were reverse coded so that a higher score represented good attitude and a lower score meant otherwise. This section was analyzed with confirmatory factor analysis (CFA) using robust maximum likelihood estimation method. The dichotomous knowledge section was scored with ‘1’ and ‘0’ point. Every correct response was given ‘1’ and an incorrect response ‘0’. This section was analyzed with 2-parameter logistic item response theory (2 -PL IRT) analysis. There were four vignettes with six response options. Intention to report was considered by the response ‘yes’ to ‘report to authority’ in at least one of the vignettes. In the second phase of the study, a cross-sectional study was conducted among early childcare providers in Kelantan to fulfill the rest of the objectives. 457 ECPs from the remaining eight districts in Kelantan participated. Data were collected using a self-administered Malay-validated version of the ECECAQ. Data were analyzed using simple and multiple logistic analyses for the second phase. Results: The Malay-validated ECECAQ had a good internal consistency reliability with Raykov’s rho value ranging from 0.672 – 0.878 for the attitude section. There was a four-factor model discovered from CFA namely perception, symptoms, support, and responsibility. The model fit on all five of fit indices (χ2 = 58.7 (48) P = 0.138; SRMR = 0.044; RMSEA = 0.033; CFI = 0.986; TLI = 0.981). Factor loadings ranged from 0.414 to 0.869. Knowledge section also had a good internal consistency with Cronbach’s alpha value of 0.65. Generally, items in the knowledge section had an acceptable difficulty and discrimination index. However, from the 2-PL IRT analysis, there were four items that did not fit the chi-square goodness-of-fit test namely K2, K4, K5c and K8. Nonetheless, they were kept because they have acceptable difficulty and discrimination index. As a whole, the knowledge section fits on two-way margins with the ratio of the standardized residual between 1.34 to 3.25, The model was unidimensional with P≥ 0.05. In phase two, 41.6% of the respondents have the intention to report child abuse. Knowledge was found to be associated with the intention to report Kelantan (OR 1.179, 95% CI: 1.066, 1.302, p=value 0.01). The respondents did well in general knowledge of child abuse compared to reporting or legal knowledge of child abuse. The question with the least correct answer was K14 which was about important criteria to report child abuse. 80% of respondents have not received any training on child abuse. About 80% of respondents had a poor attitude towards responsibility to report while more than 50% agree with the rights of parents to inflict corporal punishment towards their children. Conclusions: This study provides valid and reliable tools to measure knowledge and attitude of ECPs towards child abuse and its reporting as well as their intention to report child abuse. Findings from this study emphasized the need for a theory-based training module for ECPs regardless of agencies to improve understanding and awareness of reporting child abuse.